Pembuktian Penipuan Perdagangan Efek dalam Tindak Pidana Pasar Modal - Opit, Syaloomita Electra; Frans, Mardian Putra (SIGn Jurnal Hukum, 2025)
The criminal offense of securities trading fraud seriously threatens the integrity of the Indonesian capital market. Nevertheless, its proof within the realm of criminal law faces significant constraints. This research aims to analyze the normative evidentiary model for securities trading fraud, identify the fundamental challenges in its implementation in Indonesia, and examine strategies to overcome these obstacles. This study utilizes a normative legal research method with statutory and conceptual approaches to scrutinize the legal framework and evidentiary practices. The analysis reveals that proof formally adheres to the theory of negative statutory proof (negatief wettelijke bewijstheorie) based on the Criminal Procedure Code, requiring a minimum of two valid pieces of evidence and an evidence-based judge’s conviction. Nevertheless, the implementation of this model is confronted by multidimensional challenges, encompassing the complexity of criminal schemes, information asymmetry, difficulties in proving criminal intent (mens rea), limitations in the regulatory framework and oversight effectiveness, and constraints in accessing crucial data. This study finds that effective strategies to address these barriers necessitate a combination of interventions in two domains: strengthening substantive regulations, particularly enforcing information disclosure obligations discipline by the FSA, and enhancing transparency and accountability at the corporate level through GCG implementation and shareholder rights protection. It is concluded that a significant gap exists between the normative evidentiary model and the reality of its practical enforcement, and the effectiveness of proving securities trading fraud heavily relies on the synergy between strengthening the formal legal framework and improving the corporate governance ecosystem.